2011
DOI: 10.1128/aem.02448-10
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Diversity of Gallionella -Like Neutrophilic Iron Oxidizers in a Tidal Freshwater Marsh

Abstract: Microbial iron oxidation is an integral part of the iron redox cycle in wetlands. Nonetheless, relatively little is known about the composition and ecology of iron-oxidizing communities in the soils and sediments of wetlands. In this study, sediment cores were collected across a freshwater tidal marsh in order to characterize the iron-oxidizing bacteria (FeOB) and to link their distributions to the geochemical properties of the sediments. We applied recently designed 16S rRNA primers targeting Gallionella-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 50 publications
0
28
4
Order By: Relevance
“…The oxidation of organic matter with the reduction of Fe(III) is one of the most important redox reactions in anoxic environments (Hori et al 2010;Bongoua-Devisme et al 2013). Wang et al (2011) have confirmed that Fe(II)-oxidizing bacteria (FeOB) are ubiquitous in wetland sediments. Fe(III) oxides, such as poorly crystalline ferrihydrite produced by FeOB, were shown to be suitable for dissimilatory Fe(III)-reducing bacteria (FeRB) (Straub et al 1998;Blothe and Roden 2009).…”
Section: Introductionmentioning
confidence: 88%
“…The oxidation of organic matter with the reduction of Fe(III) is one of the most important redox reactions in anoxic environments (Hori et al 2010;Bongoua-Devisme et al 2013). Wang et al (2011) have confirmed that Fe(II)-oxidizing bacteria (FeOB) are ubiquitous in wetland sediments. Fe(III) oxides, such as poorly crystalline ferrihydrite produced by FeOB, were shown to be suitable for dissimilatory Fe(III)-reducing bacteria (FeRB) (Straub et al 1998;Blothe and Roden 2009).…”
Section: Introductionmentioning
confidence: 88%
“…Among these sequences a large proportion affiliated with purple sulfur bacteria (Chromatiaceae; typical inhabitants of stagnant pools) and versatile heterotrophs such as Pseudomonas and Xanthomonas-like organisms, followed by sulfur-oxidizing phototrophs such as Lamprocystis, and one sequence distantly affiliated to methanotrophic organisms such as Methylocaldum(Figure S3). They were closely related to communities found in solar salterns[1,2], waters and sediments of freshwater reservoirs[55,83], wetland soils as well as karst and phreatic sinkholes and deepsea marine sediments[82]. Eleven clones (5.6%) affiliated to Alphaproteobacteria that were composed in essence of Sphingomonadaceae and Rhodobacteraceae-like organisms.Epsilonproteobacteria, constituting 2.1% of the Carrizo Lake bacterial clones, were affiliated to organisms distantly related to chemolithotrophic Sulfurovum litotrophicum and Sulfurimonas autotrophica, both involved in the redox sulfur cycle, and to uncultured bacteria from activated wastewater sludges.…”
mentioning
confidence: 89%
“…Anoxic lake sediments from around the world, including those from saline and alkaline soda lakes [2,72], hypersaline lakes [73], athalassohaline lakes [28], shallow suboxic-to-anoxic freshwater ponds [5], sulfurous karstic lake [44], eutrophic lakes -including shallow [17,48,74,76], sulfur-rich minerotrophic peatlands [31], warm monomictic and meso-eutrophic lakes [68,69], freshwater tidal marshes [82], meromictic lakes [39,42], as well as metal miningimpacted lakes [8,13,19,59], have been studied, but most of this interest is centred on their phylogeny. Most of the communities were dominated by (un)culturable methane-producing archaea Methanomicrobiales, Methanobacteriaceae and Methanosarcinales and Crenarchaeota from uncultivable groups such as Miscellaneous Crenarchaeota group, Marine Group I, Marine Benthic Group B and C, Freshwater group, Group I3 and Rice Clusters IV and VI.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of Fe in biogeochemical redox cycles and its role as a potential microbial energy source, considerable research efforts have been invested in aiming to reveal the nature and numbers of ferrous iron Fe(II)-oxidizing bacteria (FeOB) in the environment (for example Ghiorse, 1984; Emerson and Weiss, 2004; Wang et al, 2009, 2011). …”
Section: Introductionmentioning
confidence: 99%